Establishment of the BioID method in Entamoeba histolytica for the characterization of the putative pathogenicity factor EHI_127670 - Arne Hellhund (2022)
The enteric protozoan parasite E. histolytica is a human pathogen causing amebiasis, a neglected tropical disease that affects nearly 50 million people and causes more than 55,000 deaths annually worldwide. The invasive form of amebiasis is characterized by the invasion of the parasites into the host intestinal tissue, which leads to amoebic colitis or abscesses in other organs, particularly the liver. The exact circumstances that lead to invasive amebiasis are unknown. Proteins that are involved in the virulence of the parasite, so called pathogenicity factors, are expected to have an influence. Recently, the new putative pathogenicity factor EHI_127670 was discovered. Phenotypic characterizations proved its enhancing influence on pathogenicity. However, structure, function, locus and interaction partners of this molecule remain unknown. It was hypothesized that the role of EHI_127670 in pathogenicity may be defined by its interaction with other pathogenicity factors. Aim of this work was the characterization of EHI_127670 by the implementation of BioID in E. histolytica, a method that detects interactions partners of a protein by biotinylating them with the protein BirA*, which is fused to the protein of interest. First, to determine the gene product of ehi_127670, the gene was expressed under its own promoter in a myc-tag expression vector in E. histolytica. Western blotting and immunofluorescence microscopy (IFA) identified EHI_127670 as a protein, localized in small, spherical vesicles, termed undefined granulae. For BioID, the expression of BirA* failed, presumably because of its bacterial origin. However, the expression of the EHI_127670:BirA* fusion protein succeeded and biotinylation experiments were performed. A strong non-specific biotinylation was observed in the BioID transfectants and the control, presumably by the presence of an unknown biotinylating protein in E. histolytica. However, after subtraction of the noise signal, seven potential interaction partners of EHI_127670 were detected in the pellet fraction. The localization of the fusion protein by IFA failed, assumably because of a massive noise signal caused by fragments of the protein in the cytosol. The BioID method was established successfully, but needs to be optimized by implementation of a suitable control, the reduction of unspecific biotinylation, and the localization of the fusion protein, before the detected potential interaction partners and thereby EHI_127670 itself may be characterized.
Keywords: Entamoeba histolytica; amebiasis; BioID; EHI_127670; pathogenicity